Iowa RBA, September 9, 1996 - Fuller, James L.et al; Johnson, Annet al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for September 9, 1996. Highlights of the update include a Black-throated Blue Warbler, two Snowy Egrets, and immature Little Blue Herons. Included are handwritten notes for the next week's update with sightings of a Yellow-rumped Warbler, a Red-necked Phalarope, and a Ringed Turtle-Dove. Also included is an email from Ann Johnson to James L. Fuller regarding multiple bird sightings, September 12, 1996. Epson - sheet feed/flatbed